2014
DOI: 10.1111/cpf.12170
|View full text |Cite
|
Sign up to set email alerts
|

Changes in circulating cytokines and markers of muscle damage in elite cyclists during a multi‐stage competition

Abstract: The purpose of this study was to determine the changes in the basal and post-exercise plasma markers of muscular damage, lipid peroxidation and cytokines in eight male well-trained semiprofessional cyclists, in response to a three consecutive-day cycling competition. Serum markers of oxidative and muscular damage - creatine kinase activity, lactate dehydrogenase activity, myoglobin and malondialdehyde (MDA), creatinine and nitrite levels - followed a sawtooth-type representation throughout the competition. MDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
2
15
0
1
Order By: Relevance
“…Originally, the IR interventions, demonstrated cardiac and skeletal injury protection after prolonged ischemic insult [ 10 ], which is associated with an increase in tissue biomarkers (e.g., creatine kinase) [ 10 ] and oxidative damage [ 11 ]. These markers are similar to those found after cycling exercise [ 12 ] and professional cycling races [ 3 ]. Thus, we speculated that PEIC intervention, through elevated levels of nitric oxide (NO), could attenuate tissue and oxidative injury after metabolic and muscle stresses caused by cycling exercise.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Originally, the IR interventions, demonstrated cardiac and skeletal injury protection after prolonged ischemic insult [ 10 ], which is associated with an increase in tissue biomarkers (e.g., creatine kinase) [ 10 ] and oxidative damage [ 11 ]. These markers are similar to those found after cycling exercise [ 12 ] and professional cycling races [ 3 ]. Thus, we speculated that PEIC intervention, through elevated levels of nitric oxide (NO), could attenuate tissue and oxidative injury after metabolic and muscle stresses caused by cycling exercise.…”
Section: Introductionsupporting
confidence: 84%
“…Each competition commonly consists of consecutive races (e.g., two or eight days) lasting 115–240 min each day [ 1 , 2 ]. During these high-intensity competitions, the athletes deal with short recovery periods between trials (e.g., 24 h or less), which could decrease subsequent performance (i.e., hours or days later) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of blood cytokine levels in well-trained cyclists who compete in multiday races, the levels of TNF- α , IL-6, IL-2, and IFN- γ were raised following intense exercise, indicating increased inflammation, whereas the level of IL-1 β was unchanged [ 21 ]. On the last day of an eighteen-day trial, cyclists given daily ketone ester (R)-3-hydroxybutyl (R)-3-hydroxybutyrate showed a 15% higher mean power output and 25% increase in the CD4 + /CD8 + (T helper cells/cytotoxic T cells) ratio than controls [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress, muscular damage, increase in inflammation, and MS associated with a decreased performance have been all reported after exhaustive exercise performed by different athletes involved in different sports [3,38,39]. This especially over the course of the multi-day races (i.e.…”
Section: Peic Effects On Recovery Performance Creatine Kinase and Mumentioning
confidence: 99%
“…This especially over the course of the multi-day races (i.e. 2 to 7 consecutive days of competition) [3,39] and with high training volumes [40]. This phenomenon may be useful for athletes and coaches searching strategies that minimize decrements in performance or to accelerate the recovery from fatiguing efforts.…”
Section: Peic Effects On Recovery Performance Creatine Kinase and Mumentioning
confidence: 99%